The best democracy money can buy : an investigative reporter exposes the truth about globalization, corporate cons, and high-finance fraudsters - Palast, Greg. (New York : Plume, 2003)
An investigative journalist provides an expose of intrigue, financial misdeeds, and other machinations at the highest level of American politics
Jim Crow in cyberspace : the unreported story of how they fixed the vote in Florida -- The best democracy money can buy : the Bushes and the billionaires who love them -- California reamin' : deregulation and the power pirates -- Sell the Lexus, burn the olive tree : globalization and its discontents -- Inside corporate America -- Pat Robertson, General Pinochet, Pepsi-Cola and the anti-Christ : special investigative reports -- Small towns, small minds -- Kissing the whip : reflections of an American in exile -- Appendix: Your turn : resources for action
مكتبة الشيخ صالح بن عبدا لله المالك [أمين مجلس الشورى السابق
1
Keywords: Corporations -- Corrupt practices -- United States; Cosmetic techniques; Political corruption -- United States